Acute Liver Failure : Management Update - Mazumder, Md Wahiduzzaman; Begum, Fahmida; Karim, ASM Bazlul (Bangladesh Journal of Child Health, 2017)
Acute liver failure (ALF) is a rare but challenging clinical syndrome with multiple causes; about 50% of pediatric cases a specific etiology cannot be identified. The course of ALF is variable and the mortality rate is high. Liver transplantation is the only therapy of proven benefit, but the rapidity of progression and the variable course of ALF limit its use. Management requires a multidisciplinary approach and is directed at establishing the etiology where possible and monitoring, anticipating, and managing the multisystem complications that occur in children with ALF. Excellent intensive care is critical in management of patients with ALF. Nonspecific therapies are of unproven benefit. Future possible therapeutic approaches include N-acetylcysteine, hypothermia, liver assist devices, and hepatocyte transplantation. Advances in stem cell research may allow provision of cells for bioartificial liver support. ALF presents many challenging opportunities in both clinical and basic research. Bangladesh J Child Health 2017; VOL 41 (1) :53-59